Дослідження пізньопалеолітичної пам’ятки біля с. Кам’янка - Сніжко, І.А. (Археологічні дослідження в Україні, 2010)
In 2009, research of a settlement near Kamianka village of Izyum Region in Kharkiv Oblast was ongoing. Planigraphic structure and character of stone inventory allow the author to define it as a workshop settlement with one-act forming of cultural layer and to refer it to the end of the Late Palaeolithic Age.